Possible Role of Bacterial and CMV Infections in Miscarriages - H. Hadi, Intisar; N. Hasan, Hanaa; A. Bunyan, Hiyam (International Journal of Psychosocial Rehabilitation, 2020)
Background: Miscarriages are considered to be the most common complication in pregnancy. The incidence of miscarriages in clinically established pregnancies (over the sixth gestational week) is approximately 12%–15%. Several possible causes of miscarriage have been considered, the major ones being genetic abnormalities of the fetus. It has been established that more than 50% of miscarried fetuses are genetically abnormal.Aim of study: To determine the role of CMV and bacterial infections in miscarriages in Hilla city.Methods: One hundred thirty (130) samples of blood and high vaginal swabs were collected from married women with vaginosis who visited the hospital of Babylon City and private clinics with ages ranging from 18 to 47 years. All the patients and control sera were screened for IgG antibodies to CMV, which is useful to detect previous exposure to CMV. Cervical swab/secretion was inoculated into nutrient agar and was incubated at 37°C for 24 hours aerobically. The isolates were identified on the basis of colony morphology from colony Gram staining, and colonies were identified as negative and positive isolates in the compacted-vatik-2 system. Some bacteria were detected by the PCR technique.Results: The higher concentration of IgG at age group (18-23) and at age group (24-29) is about 73.52600 ± 2.663314 and 55.69333 ± 2.904884, respectively, and there is an absence of IgM level. The highest rate of isolation of bacteria from vaginitis in women with abortions is Lactobacillus at 22 (33.84%), followed by Escherichia coli at 10 (15.38%), Staphylococcus aureus at 10 (15.38%), Staphylococcus pyogenes at 7 (10.76%), Proteus at 5 (7.69%), Pseudomonas aeruginosa at 4 (6.17%), Streptococcus agalactiae at 4 (6.15%), and Listeria monocytogenes at 3 (4.62%).Conclusion: CMV and bacterial infection played important roles in miscarriages.